Research methods in intercultural communication. a practical guide - Nguyen, Thi Thuy Linh (H. : ĐHQGHN, 2020)
This book is the contributory collection of a global team of experienced scholars and researchers from intercultural communication, anthropology, education, applied linguistics, and communication, explain both established and emerging research methods and analytical tools. It seeks to provide an introduction to the key methodological issues and concerns in the study of Intercultural Communication for students on advanced undergraduate and postgraduate programs in Intercultural Communication, language and linguistics, applied linguistics, TESOL, education, translation, communication studies and other related subjects.